Characteristics of lymphocyte subpopulations in the peripheral blood and lymph nodes of patients with ovarian cancer - I. Zh. Shubina; A. N. Gritsay; L. T. Mamedova; A. V. Sergeev; S. A. Kuznetsov; N. R. Pogosyan; N. I. Lazareva; M. V. Kiselevsky (ABV-press, 2014)
More and more data suggest that ovarian cancer (OC) is an immunogenic tumor. Clinical trials dealing with immunotherapy based on activated natural killer (NK) cells and dendritic cells (DC) are under way. Mononuclear cells (MNCs) from both peripheral blood and lymph nodes (LN) are proposed to be used as a source of immunity effectors. This paper characterizes peripheral blood and LN effector cells in patients with OC. The peripheral blood displayed T cell subpopulations: T helper cells, cytotoxic T lymphocytes, and NK cells. LN showed virtually no expression of NK cell antigens, but exhibited the expression of markers of DC and T regulatory cells at the same time. The cytotoxic activity of MNCs against autologous tumor cells was higher than that against the K562 cell line. OC tissue samples were observed to contain low tumor-infiltrating lymphocyte counts.